Problems encountered in LC-MS/MS analysis for the determination of pesticide residues in food - MILIADIS, G.; TSIANTAS, P.; SIRAGAKIS, G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The most common problems encountered in LC-MS/MS analysis of food are cases of compounds with low recovery, low sensitivity in one transition, common transition with matrix or other analytes, as well as solvent and matrix effects. The significance of each case was experimentally investigated in this study by the use of representative compounds. The QuEChERS approach was used for the extraction of pesticides. The study involved analysis of 128 pesticides representing various chemical classes, polarities and molecular masses, in 8 products representing different commodities of food matrices. Blank matrices fortified at 33.3 and 167 μg/kg, were analysed using different LC-MS/MS conditions in order to evaluate the significance of each parameter. Additionally long term LC-MS/MS system suitability data of 18 months were used to evaluate the variability of retention time and ion ratio at the limit of detection. This was assessed by the use of 6 representative compounds and the respective control charts.